Clinical Presentation, Videostroboscopic Features and Acoustic Analysis of Vocal Fold Cysts - Lan, Hoang; Dinh Thi, Dao; Tuan Son, Nguyen; Ngoc Ha, Nguyen; Nhu Dua, Nguyen; Van Dien, Nguyen (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 42 No 2, 2025)
Abstract: Objective: To describe clinical characteristics, stroboscopic findings, and voice acoustic parameters in patients with vocal fold cysts. Methods: A prospective descriptive case series was conducted at the National Otorhinolaryngology Hospital from October 2024 to August 2025. All patients were diagnosed with vocal fold cysts and evaluated by videostroboscopy combined with acoustic voice analysis. Results: Among 33 patients, vocal fold cysts were most common in the 41–60 age group (45.5%), with a female predominance (54.5%) and 60.6% belonging to voice-demanding occupations. Hoarseness was the most frequent symptom (100%). Lesions were mainly located at the middle third and free edge of the vocal fold. Stroboscopic findings showed reduced amplitude (33.3%), asymmetry (48.5%), and incomplete glottic closure (84.8%), often presenting a “hourglass” configuration. Mean preoperative acoustic parameters were jitter 0.76 ± 0.52%, shimmer 4.57 ± 3.20%, and HNR 28.71 ± 4.37 dB. Conclusion: Vocal fold cysts commonly occur in middle-aged women, particularly in voice professionals. Hoarseness is the characteristic symptom, with lesions typically involving the middle third of the vocal fold. Acousticopic and acoustic analyses demonstrate reduced amplitude, asymmetry, and instability of vocal fold vibration, consistent with the pathophysiology of subepithelial lesions. Keywords: Vocal fold cysts; Laryngostroboscopy; Acoustic analysis; Voice quality.